2019
DOI: 10.1371/journal.pntd.0007902
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi transmission dynamics in a synanthropic and domesticated host community

Abstract: Trypanosoma cruzi is the causative agent of Chagas disease, a Neglected Tropical Disease affecting 8 million people in the Americas. Triatomine hematophagous vectors feed on a high diversity of vertebrate species that can be reservoirs or dead-end hosts, such as avian species refractory to T. cruzi. To understand its transmission dynamics in synanthropic and domesticated species living within villages is essential to quantify disease risk and assess the potential of zooprophylaxis. We developed a SI model of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 99 publications
1
17
0
Order By: Relevance
“…dogs and chickens) were assumed to increase bug carrying capacity (Spagnuolo et al ., 2012; Peterson et al ., 2015). Other modelling approaches also supported that increasing the number of dogs would amplify the intensity of domestic transmission (Fabrizio et al ., 2016; Flores‐Ferrer et al ., 2019). The latter model, fitted to the specific eco‐epidemiology of T. dimidiata and T. cruzi in Yucatan (Mexico), predicted that a large increase in the number of chickens would decrease bug and human infection in the long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…dogs and chickens) were assumed to increase bug carrying capacity (Spagnuolo et al ., 2012; Peterson et al ., 2015). Other modelling approaches also supported that increasing the number of dogs would amplify the intensity of domestic transmission (Fabrizio et al ., 2016; Flores‐Ferrer et al ., 2019). The latter model, fitted to the specific eco‐epidemiology of T. dimidiata and T. cruzi in Yucatan (Mexico), predicted that a large increase in the number of chickens would decrease bug and human infection in the long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the population must be aware of the potential risk of keeping sylvatic rodents as pets or for hunting-information provided by local people. For T. cruzi transmission by T. dimidiata in the Yucatan peninsula, Mexico, Flores-Ferrer and cols [37] developed sophisticated models of T. cruzi transmission in a multi-host combination. They suggested that vector reproduction and parasite transmission depend on the triatomine bloodfeeding preference.…”
Section: Discussionmentioning
confidence: 99%
“…cruzi transmission by T . dimidiata in the Yucatan peninsula, Mexico, Flores-Ferrer and cols [ 37 ] developed sophisticated models of T . cruzi transmission in a multi-host combination.…”
Section: Discussionmentioning
confidence: 99%
“…However, epidemiological models suggest that infected hosts are likely to transmit T. cruzi to vectors given sufficient time and vector abundance. That is, one infected human infects 21 vectors on average while 100 vectors on average are needed to infect one human [37,38]. By sampling T. cruzi primarily from vectors we likely capture the least biased representation of the diversity in the city in order to determine how a single population of T. cruzi migrated through Arequipa.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%